A travelling-wave strategy for plant–fungal trade - Loreto Oyarte Galvez; Corentin Bisot; Philippe Bourrianne; Rachael Cargill; Malin Klein; Marije van Son; Jaap van Krugten; Victor Caldas; Thomas Clerc; Kai-Kai Lin; Félix Kahane; Simon van Staalduine; et al. (Nature, 2025)
Abstract For nearly 450 million years, mycorrhizal fungi have constructed networks to collect and trade nutrient resources with plant roots1,2. Owing to their dependence on host-derived carbon, these fungi face conflicting trade-offs in building networks that balance construction costs against geographical coverage and long-distance resource transport to and from roots3. How they navigate these design challenges is unclear4. Here, to monitor the construction of living trade networks, we built a custom-designed robot for high-throughput time-lapse imaging that could track over 500,000 fungal nodes simultaneously. We then measured around 100,000 cytoplasmic flow trajectories inside the networks. We found that mycorrhizal fungi build networks as self-regulating travelling waves—pulses of growing tips pull an expanding wave of nutrient-absorbing mycelium, the density of which is self-regulated by fusion. This design offers a solution to conflicting trade demands because relatively small carbon investments fuel fungal range expansions beyond nutrient-depletion zones, fostering exploration for plant partners and nutrients. Over time, networks maintained highly constant transport efficiencies back to roots, while simultaneously adding loops that shorten paths to potential new trade partners. Fungi further enhance transport flux by both widening hyphal tubes and driving faster flows along ‘trunk routes’ of the network5. Our findings provide evidence that symbiotic fungi control network-level structure and flows to meet trade demands, and illuminate the design principles of a symbiotic supply-chain network shaped by millions of years of natural selection.